2001
DOI: 10.1007/s002590100565
|View full text |Cite
|
Sign up to set email alerts
|

Antithyroid drugs as a factor influencing the outcome of radioiodine therapy in Graves' disease and toxic nodular goitre?

Abstract: There is controversy over the factors that may influence the outcome of radioiodine therapy for benign thyroid diseases. Antithyroid medication has been claimed to negatively influence the effectiveness of radioiodine therapy in Graves' disease. In a longitudinal study, we assessed the influence of sex, age, antithyroid drugs, target radiation dose, target mass, applied activity, delivered dose, interval between last meal and application, and TSH, FT3 and FT4 levels on the outcome of radioiodine therapy. One h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 8 publications
2
18
0
3
Order By: Relevance
“…This is because young people usually have larger goitres and higher blood concentrations of antithyroid antibodies (TRAb), which stimulate hyperthyroidism [10]. Our analysis shows, in accordance with what numerous other authors have found, that neither age (P < 0.094) nor gender (p < 0.378) have a significant influence on the outcomes of the therapy [11][12][13].…”
Section: Discussionsupporting
confidence: 80%
“…This is because young people usually have larger goitres and higher blood concentrations of antithyroid antibodies (TRAb), which stimulate hyperthyroidism [10]. Our analysis shows, in accordance with what numerous other authors have found, that neither age (P < 0.094) nor gender (p < 0.378) have a significant influence on the outcomes of the therapy [11][12][13].…”
Section: Discussionsupporting
confidence: 80%
“…Thiamazoles and thiouracils have been found to reduce the success of radioiodine treatment in Graves' disease [3,5,[23][24][25][26]. In contrast, studies including both patients with Graves' disease and patients with toxic nodular goitre revealed propylthiouracil or multiple thyrostatics to have no effect in Graves' disease but an adverse influence in toxic nodular goitre [21,22]. However, the influence of simultaneous carbimazole medication alone on radioiodine therapy in toxic nodular goitre has not yet been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-thyroid drugs are routinely used in the management of both Graves' disease and toxic nodular goitre [2,21,22]. There is controversy over whether their effect on radioiodine treatment is similar in both diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to other recent studies (12,29,30) performed in order to evaluate the efficacy of 131 I therapy, we included patients with both autoimmune (Graves' disease) and non-autoimmune hyperthyroid diseases. Our finding of no radioprotection of methimazole, among patients with either Graves' disease or toxic nodular goitre, is in contrast to the findings by Körber et al (30).…”
Section: Discussionmentioning
confidence: 99%